(untitled) (Research, Society and Development, 2022)
Throughout the coronavirus pandemic, some teaching practices needed to be adapted so that higher education could take place in a way that guarantees the continuity of quality learning, which has led many universities to explore alternative remote teaching tools. This research aimed to carry out a narrative literature review using studies published on scientific bases and whose content is related to the practices adopted during the pandemic with regard to higher education during health and biological sciences in the pandemic period. For this, articles published in the SCIELO and Google Scholar databases were considered using the following descriptors: “graduation”, “pandemic”, “coronavirus”, “biological sciences” and “health sciences”. As an inclusion criterion, only articles published between 2018 and 2022, which were in Portuguese and which dealt with the proposed topic, were considered. The use of a Virtual Learning Environment (VLE), virtual anatomy and histology laboratories from free websites, virtual meetings of academic leagues, in addition to the application of clinical cases, anatomical drawings and the construction of online concept maps were the main activities cited in the articles included in this review. It was observed that all activities were linked to a virtual learning device where teachers needed to improve their skills to perform such methodologies satisfactorily. It is also worth mentioning the fact that the Brazilian socioeconomic abyss accentuated some inequalities related to internet access by university students.